Pecel Madiun dalam Perspektif Etnomatematika: Analisis Filosofi dan Rasio Bumbu Tradisional - Nency Surya Andini (Galois: Jurnal Penelitian Pendidikan Matematika, 2026)
ABSTRACT This study aims to explore the mathematical values ​​and cultural philosophy contained in the process of making Pecel Madiun seasoning through an ethnomathematics perspective. The background of this study begins with the view that local cultural practices can represent mathematical concepts that exist in society. This study uses a qualitative approach with ethnographic methods. The subject of the study is a seller and maker of traditional Pecel Madiun who has been selling for more than 25 years in Madiun City, East Java. Data were collected through participant observation, in-depth interviews, and documentation, then analyzed using the interactive model of Miles, Huberman, and Saldaña. The results show that the process of making Pecel Madiun seasoning contains the application of the concept of ratio and equivalent comparison that emerges intuitively. The composition of ingredients such as peanuts, dried chilies, brown sugar, white sugar, lime leaves, and salt is arranged in certain proportions that are passed down from generation to generation to maintain a balance of taste. The balance between spicy and sweet flavors reflects the life philosophy of the Madiun people about harmony and simplicity, which can be interpreted as a form of mathematical representation in a cultural context. These findings indicate that local culture has great potential as a source of contextual mathematics learning that is relevant and meaningful for students. Keywords: ethnomathematics, Pecel Madiun, ratio, balance, cultural philosophy